Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Keywords: Europe; Libre accès; Rôle des universités